Impact of burning crop residues on mycorrhizal fungi in soil, urease activity, and mung bean (Vigna radiata (L.) R. Wilczek) growth - Kadhem, W. A.; Hussein, K. A.; Abud, A. H. (Scientific Progress & Innovations, 2025)
This research focuses on the effect of burning crop residues on the total number of spores of mycorrhizal fungi, the activity of some soil enzymes, and the growth of the mung bean (Vigna radiata), in which 12 soil samples were collected before and after burning plant residues, one sample every 15 days, in addition to estimating the enzyme activity of urease (urea aminohydrolase, EC 3.5.1.5). The Completely Randomized Design (CRD) was used. Data were analyzed statistically using the computer, and LSD values were used to compare the averages of the coefficients at the 0.05 probability level in all experiments. Results shown a significant decrease in the number of mycorrhiza spores, as the first burning period recorded a percentage of 22.7 %, while the second period recorded a non-significant decrease of 2.5 %. As for the urease enzyme, a significant increase in its activity was observed with an increase of 22.9 % after the first period of burning, followed by a decrease of 24,0 % during the second. To determine the impact of burning crop residues on the germination and growth of mung bean, its seeds were grown in plastic containers containing burned and unburned soil under recorded conditions of light, humidity and temperature for 15 days, the results shown a decrease in the germination rate of seeds planted in burned soil as well as the dry root weight and the seedling vigor, while both the seedling dry root weight of the seedling and height increased. In response to burning, the chlorophyll A, B, and total chlorophyll content in mung bean leaves grown in burned soil was lower than that in unburned soil. Thus, burning plant residues led to a reduction in the number of mycorrhizal fungi, affected urease enzyme activity (which did not recover even after three months), and had an adverse effect on soil enzymes, although burning stimulated certain aspects of mung bean growth as measured by dry mass and chlorophyll content.